DESKRIPSI KESALAHAN MENULIS PADA TEKS KARANGAN SISWA KELAS V SEKOLAH DASAR NEGERI 09 PONTIANAK BARAT - Oei Fira Ramadhani; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Universitas Tanjungpura, 2021)
AbstractThis research aimed for describing student's essay text writing mistake at 5th grade class atSekolah Dasar Negeri 09 Pontianak Barat. This researchs using qualitative approach withdescriptive method. Data sources in this research is from 31 students of 5th grade class A atSekolah Dasar Negeri 09 Pontianak Barat. The instrument in this research using humaninstrument, which the data collection method is from documentation method and reading &writing method. Miles model and Huberman has 3 steps, including data reduction, dataserving and conclusion, used for data analysis technique. The data validity techniques usingtechnique increasing persistence by reading the essay text over and over again. The result ofdata colleting shows 2083 mistake from 26 essay text. The writing mistake divided into (1)speeling mistake shows 1850 mistakes or 88,81%, (2) the choosing word mistake shows 92mistakes or 4.42% and (3) the effective sentences writing mistakes shows 141 mistakes or6,77%.Keywords: Bahasa Indonesia, Essay Text, Writing Mistakes